Evaluating plantar biomechanics while descending a single step with different heights - Guo, Panjing; Zhang, Xiajing; Xu, Haoran; Wang, Ruiqin; Li, Yumin; Xu, Chengshuo; Yang, Yu; Zhang, Linlin; Adams, Roger; Han, Jia; Lyu, Jie (Frontiers in Bioengineering and Biotechnology, 2024)
Objective: This study aims to investigate the plantar biomechanics of healthy young males as they descend a single transition step from varying heights. Methods: Thirty healthy young males participated the experiment using the F-scan insole plantar pressure system in which participants made single transition steps descent from four step heights (5cm, 15 cm, 25cm, and 35cm), leading with their dominant or non-dominant foot. Plantar pressure data were collected for five seconds during the period between landing touchdown and standing on the ground. Landing at each step height was repeated three times, with a five-minute rest between different height trials. Results: At 5 cm and 15 cm steps, participants demonstrated a rearfoot landing strategy on both sides. However, forefoot contact was observed at heights of 25 cm and 35 cm. Parameters related to center of plantar pressure (COP) of the leading foot were significantly larger compared to the trailing foot (P<0.001), increased with higher step heights. Vertical ground reaction forces for the biped, leading and trailing feet decreased with increasing step height (all P<0.05). The leading foot had a higher proportion of overall and forefoot loads, and a lower proportion of rearfoot load compared to the trailing foot (P<0.001). The overall load on the dominant side was lower than that of the non-dominant side for both the leading and trailing feet (P<0.001). For the trailing foot, forefoot load of the dominant side was lower than that of the non-dominant side, however, the opposite result appeared in rearfoot load (P<0.001). Upon the leading foot landing, forefoot load exceeded the rearfoot load for the dominant (P<0.001) and non-dominant sides (P<0.001). Upon the trailing foot landing, forefoot load was lower than the rearfoot load for the dominant (P<0.001) and non-dominant sides (P=0.019). Conclusion: When the characteristics of biomechanical stability are compromised by step height, landing foot, and footedness factors—due to altered foot landing strategies, changing COP, or uneven force distribution—ability to control motion efficiently and respond adaptively to the forces experienced during movement is challenged, increasing the likelihood of loss of dynamic balance, with a consequent increased risk of ankle sprains and falls.